(untitled) (African Multidisciplinary Journal of Research, 2023)
The entry of Christianity into Uganda to liberate mankind from thorny cultural life challenges was initiated by Kabaka Mutesa 1. Since the 19th century, Christianity has had colourful influences on indigenous communities, including, art, politics, family life, music, business, and the way people express their cultural thoughts. In Uganda, missionaries presented white culture Christianity that demonised the religiosity of indigenous people. They perceived black culture as primitive and religiosity of indigenous people as an empty page that had no historical encounter with the divine. This was a misconception; Ugandans were creative and well informed in all life spheres. Organized cultural and political systems that provided fertile ground for seeds of Christianity to germinate and flourish were already in place. Missionaries were God-sent to complement on the Garden of Eden and the Tower of Babel instituted cultural artistic works that were oscillating and had been spinning for generations. The primary seeds of Christianity germinated and had a great impact on the Ugandan society. However, indigenous people were reflected in literary works and reports as consumers of missionary programmes but not co-partners in the propagation process. Other than Kabaka Mutesa 1, the voices of the parliamentarians are non-existent in European missionary literary works. Indigenous people contributed their time and skills as: guides, casual labourers, hosts, interpreters, translators, providers of meals, land donors, vernacular teachers, producers of raw materials, and consumers of imported exotic products, but their faces are not reflected in the missionary success documented works. In the process of Christianity propagation, martyrdoms were registered. The deadly scenarios were attributed to the brutal leadership of the young king, Mwanga. However, scanning through the events that surrounded martyrdoms, it is conclusive that missionaries propelled the massacres due to their inability to immerse themselves in the host culture and understand indigenous social traditions.